CO2 induced phase transitions in diamine-appended metal–organic frameworks1. Issue 9 (10th September 2015) - Vlaisavljevich, Bess; Odoh, Samuel O.; Schnell, Sondre K.; Dzubak, Allison L.; Lee, Kyuho; Planas, Nora; Neaton, Jeffrey B.; Gagliardi, Laura; Smit, Berend
<x xml:space="preserve">Abstract</x> Using a combination of density functional theory and lattice models, we study the effect of CO2 adsorption in an amine functionalized metal–organic framework.